Gas-phase elemental mercury removal by bamboo charcoal impregnated with KMnO4: mechanism study. Issue 4 (July 2021) - Tan, Zengqiang; Niu, Guoping; Li, Yuanhao; An, Xiaoxue
Abstract: Bamboo charcoal is made from biomass with porous structure. The performance of bamboo charcoal (BC) and KMnO4 -modified BC was studied with a bench-scale fixed-bed reactor. X-ray photoelectron spectroscopy, X-ray diffraction, elemental analysis and BET surface area analysis were used to determine the physical and chemical property of the sorbents. The results show that the modification increased the oxygen functionalities and π electrons, which facilitate the mercury oxidation on sorbent surface and act as possible active centers for elemental mercury.